Provenance, volcanic record, and tectonic setting of the Paleozoic Ventania Fold Belt and the Claromecó Foreland Basin: Implications on sedimentation and volcanism along the southwestern Gondwana margin - Alessandretti, Luciano (2013)
This study focuses on the provenance, volcanic record, and tectonic setting of the Paleozoic Ventania System, a geologic province which comprises the Cambro-Devonian Ventania Fold Belt and the adjoining Permo-Carboniferous Claromecó Foreland Basin, located inboard the deformation front. The Ventania Fold Belt is formed of the Curamalal and Ventana groups, which are composed mainly of mature quartzites that were unconformably deposited on igneous and metamorphic basement. The Pillahuincó Group is exposed as part of the Claromecó Basin and it has lithological and structural features totally distinct from the lowermost groups. This group is composed of immature arkoses and subarkoses with intercalated tuff horizons, unconformably overlaying the quartzites and associated with glacial-marine deposits of the lower Late Carboniferous to Early Permian section. The petrography, as well as major and trace elements (including rare earth elements) support that the Ventania quartzites were derived from cratonic sources and deposited in a passive margin environment. For the Pillahuincó Group, we suggest a transition between rocks derived from and deposited in a passive margin environment to those with geochemical and petrographical signatures indicative of an active continental margin provenance. LA-MC-ICP-MS analysis performed on euhedral and prismatic zircon grains of the tuffs revealed an age of 284 ± 15 Ma. The geochemical fingerprints and geochronological data of the tuffs found in the Claromecó Basin support the presence of an active and widespread Lower Permian pyroclastic activity in southwestern Gondwana, which is interpreted as part of the Choiyoi Volcanic Province in Argentina and Chile.